STUDI KUALITATIF POLA BERPASANGAN (Sexual Partnership) PADA PUS DALAM PENCEGAHAN PENULARAN HIV DI KOTA KEDIRI - Eny Sendra; Arika Indah Setyarini; Indah Rahmaningtyas (Poltekkes Kemenkes Malang, 2020)
HIV is an infectious disease which is attacks the immune system. HIV is related with sexual healht and reproductive health who not achieved, that is how sexual elements work in certain socio cultural settings giving rise to health implications on the person. This study aims to determine of sexual partnership in reproductive age couples to preventing HIV Transmission At City of Kediri. This research is a descriptive study with a qualitative approach. Participants in this study were 12 Reproductive Age Couples which taken using purposive sampling technique. Data collection uses a process of in depth interviews, Focus Group Discussion or FGD and Observation of Couple Patterns or Sexual Partnership. The results showed that the characteristics of sexual partnership are oriented toward marital status and consensual relationships with one another accepting and needing as an increase in quality of life, commitment to mutual trust, reducing stress, and reducing the risk of sexual behavior at risk of a partner. The success of HIV transmission prevention efforts is highly dependent on various parts, not only the active role of health workers in providing education and information about HIV, but also the support of partners and families as the main motivators to behave properly according to safe sexual relations.